Experimental model of crushing coriander seeds - N. V. Sterekhova; S. Yu. Gonezhuk; Z. A. Meretukov; M. V. Sherbakov (Новые технологии, 2024)
Seed crushing is one of the main technological operations [1] in the process of obtaining essential and fatty oils, on which their yield and quality depend [2]. Improving the process of preparation for the extraction of coriander seeds by selective cryodesintegration and creating technological lines of various productivity is of significant importance and relevance. However, modern methods and means of cryodesintegration of coriander seeds require research and improvement. The process of seed grinding is divided into three phases [3]: elastic deformation, which occurs from the beginning of the action of the applied force on the material being ground until the elastic limit is reached and is accompanied by compaction and compression of the structural aggregates of the seeds; plastic deformation, which occurs from the moment of the beginning of the shift of individual elements of the material relative to each other and is characterized by the relative displacement of the structural aggregates of the seed kernel, as a result of which the material is compacted and flattened; destruction of the material with the formation of a free surface of particles. The main parameter of the process of cryodesintegration of coriander seeds is subject to theoretical justification - normal pressure, leading to deformation, where the pressure on the seeds exceeds their tensile strength, but there is no appearance of oil on the surface of the opened seeds. This prevents oil loss and contamination of the working parts, especially with essential oils. Monitoring theoretical studies of the grinding process allows us to talk about the need to develop a mathematical description of this process.